Models, systems, networks in economics, engineering, nature and society - V.M. Volodin; T.Yu. Pashchenko; D.V. Senatorov (Модели, системы, сети в экономике, технике, природе и обществе)
Background. The results of research into control systems in clusters always arouse great interest among researchers. A lot of analytical work has been carried out on clusters in the Penza region. We saw both similarities and differences in individual clusters, where the main one is unanimous decision-making, and, conversely, in practice there are also those that are more reminiscent of other types of associations. The relevance of the study is related to solving the problems of growth of productive labor, the number of jobs, competitiveness and sustainability of the enterprise. The relevance is associated with major problems in building the interests of cluster participants aimed at increasing the competitiveness of enterprises. Undoubtedly, the main interest is to obtain increasing profits both for the association as a whole and for each individual, as well as in the sustainable operation of clusters and enterprises. Materials and methods. The study presents primary materials from enterprises and associations of the furniture cluster of the Penza region, as well as the results of the research obtained from leading specialists of associations, incl. clusters. The work used methods of clustering enterprises and identifying the main link, forms of financial support for network interregional interaction. Results. It has been proven that the interests of enterprises in joining associations (clusters) are present. This is due to the sustainability of enterprises, including in the context of a pandemic and sanctions; management in clusters does not give rise to antagonistic contradictions in comparison with other associations, but contributes to operational impact in identifying problematic issues. Conclusions. Under normal conditions, clusters are an effective form of management. However, when solving innovative problems, the dynamics of their growth remains insignificant; for participation in leapfrog growth (which today requires only individual enterprises of the association to be ready for it), the cluster as a whole is not ready.